Crosslinking electrospun poly (vinyl) alcohol fibers with citric acid to impart aqueous stability for medical applications. (5th February 2020) - Nataraj, Divya; Reddy, Roopa; Reddy, Narendra
Graphical abstract: Highlights: Poly vinyl alcohol (PVA) was electrospun into nanofibers. The nanofibers were crosslinked with green crosslinker citric acid. Crosslinking enhanced water resistance, tensile strength and thermal stability of the nanofibers. Crosslinked electrospun PVA nanofibers showed potential for cell culture applications. Abstract: In this study, the highly hydrophilic PVA was made into water-stable electrospun fibers using citric acid (CA) as a green crosslinker. Although PVA is accepted as a biocompatible polymer, poor water resistance especially when made into nano and microfibers limits its biomedical applications. Previous attempts to improve the stability and mechanical properties of electrospun PVA have either used toxic crosslinkers or expensive and tedious chemical modifications. In this research, we have developed electrospun PVA fibers and later crosslinked the fibers using citric acid. The electrospun fibers were studied for their water stability, tensile strength, elongation, morphology, thermal stability, and biocompatibility. The uncrosslinked fibers had an average diameter of 100–300 nm but disintegrated in water immediately. The crosslinked nanofibers were found to be stable in water after immersion in water even after 72 h. However, the nanoscale morphology of the fibers was not retained. The maximum strength of 7.6 MPa and elongation of 55.28% was obtained when the electrospun membranes were crosslinked with 10% CA. In addition to improved water resistance, crosslinking increased the thermal stability of the fibers with the melting temperature increasing to 194 °C from 170 °C. Also, crosslinked PVA nanofibers were stable in cell culture media for up to 96 h and supported the attachment and proliferation of NIH 3 T3 mouse fibroblast cells in time dependent manner. This study demonstrates a means to obtain PVA nanofibers and also freeze-dried scaffolds with aqueous stability and biocompatibility required for tissue engineering and other medical applications.